«Gender Studies» e bioetica di fine vita nuovi contributi e prospettive - Galvagni, Lucia (2003)
This essay is intended as an introduction to the topic of «gender studies» and bioethics: we will start by working out a number of characteristic traits of the two disciplines and try to arrive at a dialogue between the two. Moral reflection can be influenced by gender identity: gender ethics investigates these influences. The possibility of viewing subjectivity differently, by paying attention to concreteness and relationality for example, of taking on a respectful attitude, and of listening to different voices in an ethical context provides substantial pointers also for assessing and rereading the topics and the state of end-of-life bioethics.